Thomas and Emma Wakley, with their daughters Margaret and Jessie and their grandson, Arthur Wakley (1919)
This collection contains copies made in 1998 of original photographs gathered by the Haystack Reunion Committee for publication in their booklet Haystack Reflections (1997).